Modeling the carbon-energy-water nexus in a rapidly urbanizing catchment: A general equilibrium assessment. (1st November 2018) - Su, Qiong; Dai, Hancheng; Lin, Yun; Chen, Huan; Karthikeyan, Raghupathy
Abstract: Energy and water systems are interdependent and have complex dynamic interactions with the socio-economic system and climate change. Few tools exist to aid decision-making regarding the management of water and energy resources at a watershed level. In this study, a Computable General Equilibrium (CGE) model and System Dynamics and Water Environmental Model (SyDWEM) were integrated (CGE-SyDWEM) to predict future energy use, CO2 emissions, economic growth, water resource stress, and water quality change in a rapidly urbanizing catchment in China. The effects of both the CO2 mitigation strategies and water engineering measures were evaluated. CO2 mitigation strategies have the potential to reduce 46% CO2 emissions and 41% energy use in 2025 compared with reference scenario. CO2 mitigation strategies are also found to be effective in promoting industrial structure adjustment by decreasing the output of energy- and water-intensive industries. Accordingly, it can alleviate local water stress and improve water environment, including a 4.1% reduction in both domestic water use and pollutant emissions, a 16.8% water demand reduction in the labor-intensive industry sector, and 4.2% and 4.4% decrease in BOD5 and NH3 -N loads in all industrial sectors, respectively. It is necessary to implement water engineering measures to further alleviate water resource stress and improve water quality. This study improves the understanding of the feedbacks of CO2 abatement on water demand, pollutant discharges, and water quality improvement. The integrated model developed in this study can be used to aid energy, carbon, and water policy makers to understand the complicated synergistic effects of proposed CO2 mitigation strategies on water demand and pollution emissions, and to design more effective policies and measures to ensure energy and water security in the future. Highlights: An integrated model (CGE-SyDWEM) is developed to simulate the carbon-energy-water nexus. CO2 mitigation strategies are efficient in promoting industrial structure adjustment. CO2 mitigation strategies have co-benefits on water use and pollutant discharge reduction. Water engineering measures can greatly alleviate water resource stress and improve water quality.